Profitability of swine enterprises by scale of operation and production system in two hog-producing towns in Bulacan, Philippines - Aspile, Sharmaine Chantal Khaye C.; Manipol, Nohreen Ethel P.; Depositario, Dinah Pura T.; Aquino, Nanette A. (2016)
This paper compares the profitability of swine enterprises according to scale of operation and production system in two major hog-producing towns in Bulacan, Philippines. Results are based on a survey of 145 hog raisers — 71 from the City of San Jose del Monte (CSJDM) and 74 from Santa Maria. The CSJDM enterprises have higher net income per head than the Santa Maria enterprises but the latter have slightly higher profit-to-sales ratio. By scale of operation, medium commercial enterprises are the most profitable in both areas and found to have sold their produce at the highest price. Across production systems, the farrow-to-breeder-finisher in CSJDM registers the highest proportion of profit to sales. This system sells multiple products and its breeder stocks are sold at higher prices. The boar-for-hire production system has the lowest profit-to-sales ratio, which is attributed to the increasing utilization of artificial insemination in CSJDM. In the case of the Santa Maria enterprises, the farrow-to-finish production system registers the highest income on a per head basis; the lowest for the growing-finishing production system. By scale of operation, the internal factors which determine profitability are the number of hogs raised and the utilization of high-quality feeds. By production system, the critical internal factors are the types and prices of animals sold, feeds, and capital for weaners. A favorable enabling environment, including improved incentive system and accessible credit, can help promote commercial and integrated swine enterprises in the study area.
Keywords: Swine industry; Production management; Supply chain operations